The evaluation of child sexual abuse allegations: a comprehensive guide to assessment and testimony - Kuehnle, Kathryn (Wiley, 2009)
Improved forensic interviewing : the legacy of the McMartin preschool case / John Myers -- Methods for the identification of sexually abused children : overview of issues and needed features for abuse indicators / David Faust, Ana J. Bridges, and David Ahern -- Methods for the identification of sexually abused children : re-framing the clinician's task and recognizing its disparity with research on indicators / Ana J. Bridges, David Faust, and David Ahern -- Methods for the identification of sexually abused children : suggestions for clinical work and research / David Faust, Ana J. Bridges, and David Ahern -- Professional roles : key to accuracy and effectiveness / Charles Clark -- Ethical issues in child sexual abuse evaluations / Gerald Koocher -- Child development : normative sexual and non-sexual behaviors that may be confused with symptoms of sexual abuse / Debra A. Poole and Michele A. Wolfe -- The continuum of children's sexual behavior : moral and legal considerations / Kathryn Kuehnle, Jessica Gurney, and H.D. Kirkpatrick -- Normative memory development and the child witness / J. Zoe Klemfuss, Stephen Ceci, and Maggie Bruck -- Children's resistance to suggestion / Latonya Harris, Gail Goodman, Else Marie Augusti, Yoojin Chae, and Deborah Alley -- Recollections of childhood trauma : repression and recovery of memories during childhood and adolescence / Andrea Greenhoot and Monica Tsethlikai -- Forensic child sexual abuse evaluations: accuracy, ethics, and admissibility / Steve Herman -- Children's suggestibility : areas of consensus and controversy / Lindsay C. Malloy and Jodi Quas -- Interview protocols : adherence to best practice / Deirdre Brown and Michael E. Lamb -- Repeated interviewing : a critical evaluation of the risks and potential benefits / David La Rooy, Michael E. Lamb, and Margaret-Ellen Pipe -- The pros and cons of using dolls, drawing, body diagrams and other props in investigative interviews / Margaret-Ellen Pipe and Karen Salmon -- Unsupported assessment techniques in child sexual abuse evaluations / Daniel Murrie, David Martindale, and Monica Epstein -- The child advocacy center model / Mary Connell -- The extended forensic evaluation / Mary Connell -- The return of the ultimate issue : talking to the court in child sexual abuse cases / Daniel Shuman and Bill Austin -- Jurors and professionals in the legal system : what they know and what they should know about interviewing child witnesses / Julie A. Buck and Amye Warren